Trends in the Prevalence of Reduced GFR in the United States: A Comparison of Creatinine- and Cystatin C-Based Estimates - Grams, Morgan E. (2013)
BACKGROUND: The US prevalence of reduced estimated glomerular filtration rate (eGFR) based on serum creatinine increased over the decade ending in 2002. National Health and Nutrition Examination Survey (NHANES) cystatin C measurements were recently calibrated to the international standard, allowing for an independent test of the trend in prevalence of reduced eGFR using cystatin C. STUDY DESIGN: Cross-sectional surveys performed during two periods. SETTING & PARTICIPANTS: Nationally representative subsamples of adult participants from NHANES III (1988–1994) and the NHANES 1999–2002 surveys. PREDICTOR: Survey period. OUTCOMES: Prevalence of reduced GFR, defined as eGFR<60ml/min/1.73m(2) based on serum creatinine, cystatin C, or both (eGFR(cr), eGFR(cys), eGFR(cr-cys)), using estimating equations developed by the Chronic Kidney Disease Epidemiology Collaboration (CKDEPI). MEASUREMENTS: Serum cystatin C, measured from stored samples in 2006, calibrated to the international standard in 2012. RESULTS: Between 1988–1994 and 1999–2002, the prevalence of reduced eGFR(cr), eGFR(cys) and eGFR(cr-cys) increased from 4.7% (95% CI, 4.1%–5.3%) to 6.5% (95% CI, 5.9%–7.1%; p<0.001), from 5.5% (95% CI, 4.6%–6.5%) to 8.7% (95% CI, 7.5%–10.0%; p<0.001), and from 4.4% (95% CI, 3.7%–5.2%) to 7.1% (95% CI, 6.2%–8.0%; p<0.001), respectively. The higher prevalence of reduced GFR in the later period was observed in all subgroups of age, race, sex, and GFR categories. After adjusting for changes in the US population by age, sex, race, diabetes, hypertension, and body mass index, the prevalence ratio of reduced GFR in the later versus earlier survey was 1.24 (95% CI, 1.09–1.45), 1.34 (95% CI, 1.15–1.67), and 1.33 (95% CI, 1.17–1.65) using eGFR(cr), eGFR(cys), and eGFR(cr-cys), respectively. LIMITATIONS: Likely under-ascertainment of persons with GFR<15 ml/min/1.73m(2); GFR was estimated and not measured; comparability of laboratory assays based on a calibration subsample. CONCLUSIONS: The prevalence of reduced eGFR(cys) in the US civilian, non-institutionalized population increased between 1988–1994 and 1999–2002, confirming the increase observed in the prevalence of reduced eGFR(cr).